2023
DOI: 10.1111/bre.12753
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of catchment‐depositional system relationships on the dip slopes of intra‐rift basement highs: An example from the Frøya High, Mid‐Norwegian rifted margin

Abstract: Basement highs form one of many potential sediment source areas during the evolution of continental rifts and rifted margins and add to the topographic complexity typical of active rifts. Footwall basement highs acting as a source area to sedimentary systems in the hangingwall of major faults has been documented in many systems worldwide. However, the back-tilted footwall dip slopes of such highs have received comparatively little attention. Here we investigate a subsurface case study from the Norwegian contin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 89 publications
(243 reference statements)
4
9
0
Order By: Relevance
“…6407/9‐1), southwest of the Draugen Field area in well 6407/11‐1 and on the central Frøya High in wells 6306/6‐1 and 6306/9‐1 (Figure 1b). Early depositional models for the Rogn Formation from the Draugen Field area, and more recent studies of the Vingleia and Klakk fault complex, support the rift physiography shown herein, with sediment being eroded from the uplifted areas and transported back onto the footwall, down the gently dipping dipslope (Bell et al, 2014; Chiarella et al, 2020; Elliott et al, 2017, 2021; Goesten & Nelson, 1992; Gresseth et al, 2023; Henstra et al, 2023; Jones et al, 2020; Muñoz‐Barrera et al, 2021; Provan, 1992; Van der Zwan, 1990). In comparison, the Rogn Formation recorded on the Frøya High has received less attention but has been interpreted to be connected along the strike of the footwall island to age‐equivalent deposits in the Draugen Field area (Chiarella et al, 2020; Henstra et al, 2023).…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…6407/9‐1), southwest of the Draugen Field area in well 6407/11‐1 and on the central Frøya High in wells 6306/6‐1 and 6306/9‐1 (Figure 1b). Early depositional models for the Rogn Formation from the Draugen Field area, and more recent studies of the Vingleia and Klakk fault complex, support the rift physiography shown herein, with sediment being eroded from the uplifted areas and transported back onto the footwall, down the gently dipping dipslope (Bell et al, 2014; Chiarella et al, 2020; Elliott et al, 2017, 2021; Goesten & Nelson, 1992; Gresseth et al, 2023; Henstra et al, 2023; Jones et al, 2020; Muñoz‐Barrera et al, 2021; Provan, 1992; Van der Zwan, 1990). In comparison, the Rogn Formation recorded on the Frøya High has received less attention but has been interpreted to be connected along the strike of the footwall island to age‐equivalent deposits in the Draugen Field area (Chiarella et al, 2020; Henstra et al, 2023).…”
Section: Discussionsupporting
confidence: 73%
“…Seemingly isolated sandbodies of the Rogn Formation are presently identified locally in wells drilled in these uplifted areas (i.e. on the Frøya High and in the immediate footwall of the Vingleia Fault Complex; e.g, wells 6306/6‐1 and 6407/9‐1; Chiarella et al, 2020; Dalland et al, 1988; Elliott et al, 2017; Henstra et al, 2023; Provan, 1992). In the study area, the sandstone‐rich Rogn Formation typically forms coarsening‐upward, heavily bioturbated units, interpreted to be deposited in a shoreface to the offshore‐bar environment (Chiarella et al, 2020; Elliott et al, 2017; Henstra et al, 2023; Provan, 1992; Van der Zwan, 1990); however, the more regional distribution of this enigmatic unit remains poorly constrained, due to limited good coverage, seismic resolution and few regional studies (e.g.…”
Section: Geological Settingmentioning
confidence: 99%
See 3 more Smart Citations